Highly Selenite-Tolerant Strain Proteus mirabilis QZB-2 Rapidly Reduces Selenite to Selenium Nanoparticles in the Cell Membrane - Huang, JinLan; Jiang, DaiHua; Wang, MingShi; Huang, XueJiao (Frontiers in Microbiology, 2022)
The application of biosynthesized nano-selenium fertilizers to crops can improve their nutrient levels by increasing their selenium content. However, microorganisms with a high selenite tolerance, selenite reduction capacity, and the ability to produce selenium nanoparticles (SeNPs) have seldom been reported. In this study, a bacterial strain showing high selenite resistance (up to 350 mM) was isolated from a lateritic red soil and identified as Proteus mirabilis QZB-2. This strain reduced nearly 100% of 1.0 and 2.0 mM selenite within 12 and 18 h, respectively, to produce SeNPs. QZB-2 isolate reduced SeO32- to Se0 in the membrane with NADPH or NADH as electron donors. Se0 was then released outside of the cell, where it formed spherical SeNPs with an average hydrodynamic diameter of 158.6 ± 15.2 nm. P. mirabilis QZB-2 could be used to produce selenium nanoparticles efficiently, which could boost the use of nano-selenium fertilizers.